Does Prolonged Education Causally Affect Dementia Risk When Adult Socioeconomic Status Is Not Altered? A Swedish Natural Experiment in 1.3 Million Individuals. Issue 5 (23rd November 2020) - Seblova, Dominika; Fischer, Martin; Fors, Stefan; Johnell, Kristina; Karlsson, Martin; Nilsson, Therese; Svensson, Anna C; Lövdén, Martin; Lager, Anton
Abstract: Intervening on modifiable risk factors to prevent dementia is of key importance, since progress-modifying treatments are not currently available. Education is inversely associated with dementia risk, but causality and mechanistic pathways remain unclear. We aimed to examine the causality of this relationship in Sweden using, as a natural experiment, data on a compulsory schooling reform that extended primary education by 1 year for 70% of the population between 1936 and 1949. The reform introduced substantial exogenous variation in education that was unrelated to pupils' characteristics. We followed 18 birth cohorts ( n = 1, 341, 842) from 1985 to 2016 (up to ages 79–96 years) for a dementia diagnosis in the National Inpatient and Cause of Death registers and fitted Cox survival models with stratified baseline hazards at the school-district level, chronological age as the time scale, and cohort indicators. Analyses indicated very small or negligible causal effects of education on dementia risk (main hazard ratio = 1.01, 95% confidence interval: 0.98, 1.04). Multiple sensitivity checks considering only compliers, the pre-/post- design, differences in health-care-seeking behavior, and the impact of exposure misclassification left the results essentially unaltered. The reform had limited effects on further adult socioeconomic outcomes, such as income. Our findings suggest that without mediation through adult socioeconomic position, education cannot be uncritically considered a modifiable risk factor for dementia.